PERAN END CHILDREN PROSTITUTION AND TRAFFICKING (ECPAT) DALAM MENANGANI EKSPLOITASI SEKSUAL ANAK DI PATTAYA, THAILAND PASCA PANDEMI COVID-19 - Filda, Aiska; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
. This study examines the dynamics of child sexual exploitation in Pattaya and analyze ECPAT’s role in addressing sexual exploitation of children in travel and tourism (SECTT) and online child sexual exploitation (OCSE). The research employed a qualitative approach, with data collected through literature review from academic journals, books, organizational reports, and relevant online sources. The analysis was conducted through a Pluralist perspective and Civil Society Organization (CSO) theory. The results indicate that ECPAT plays a role in preventing child sexual exploitation through monitoring, advocacy, capacity building, and catalyzing change. Nevertheless, the effectiveness of ECPAT’s role in Pattaya is still affected by various structural barriers, such as suboptimal coordination between legal instituins, complex reporting procedures, and persistent social stigma that discourages disclosure. Keywords : Child Sexual Exploitation, ECPAT, CSO